2015
DOI: 10.1152/physiolgenomics.00026.2015
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the nutritional regulation of gluconeogenesis in carnivorous rainbow trout (Oncorhynchus mykiss): a gene duplication trail

Abstract: The rainbow trout (Oncorhynchus mykiss) is considered to be a strictly carnivorous fish species that is metabolically adapted for high catabolism of proteins and low utilization of dietary carbohydrates. This species consequently has a "glucose-intolerant" phenotype manifested by persistent hyperglycemia when fed a high-carbohydrate diet. Gluconeogenesis in adult fish is also poorly, if ever, regulated by carbohydrates, suggesting that this metabolic pathway is involved in this specific phenotype. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 63 publications
19
94
0
Order By: Relevance
“…mammalian G6pc, Fbp1, Gck and pfkl co-orthologues, respectively) displayed divergent patterns. These results confirmed that a sub-or neo-functionalization of these genes occurred after their duplication, as previously proposed by Marandel et al (2015).…”
Section: Studying Duplicated Glucose Metabolism-related Genes New Inssupporting
confidence: 91%
See 4 more Smart Citations
“…mammalian G6pc, Fbp1, Gck and pfkl co-orthologues, respectively) displayed divergent patterns. These results confirmed that a sub-or neo-functionalization of these genes occurred after their duplication, as previously proposed by Marandel et al (2015).…”
Section: Studying Duplicated Glucose Metabolism-related Genes New Inssupporting
confidence: 91%
“…In addition, mechanisms underlying the poor ability of carnivorous fish to use dietary carbohydrates as a major energy substrate remain poorly understood. A recent study emphasized that the fate of duplicated genes after Ss4R may participate in the initiation of the glucose-intolerant phenotype in juvenile trout fed a high-carbohydrate diet (Marandel et al, 2015). This new genomic point of view following the recent sequencing of the rainbow trout genome should provide new pathways to investigate impaired glucose metabolism in this species.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations